Interpretasi Fiqh Siyasah Pemerintahan Islam Pada Masa Al-Khulafa’ Al-Rasyidin - Shobirin Shobirin; Ahmad Rofiq; Ali Imron (LP2M IAIN kUDUS, 2023)
Abstrak This article is entitled, Interpretation of fiqh Siyasah the Pattern of Islamic Government during the Time of al-Khulafa' al-Rasyidin. The problem that was Whichresearched is related to the process of appointment of caliph at the time of al-Khulafa' al-Rasyidin, the pattern of government during the time of al-Khulafa' al-Rasyidin and the practice of Islamic government during the time of al-Khulafa' al-Rashidun. The type of research in this article is library research. Methodologically, library research is included in the qualitative research category, namely research in the form of documents and records of past events, which can be in the form of writing, drawings, or monumental works from someone regarding the history of Islamic government in the era of al-Khulafa' al-Rasyidin. This research uses two approaches adapted to the problems discussed, namely the analytical and historical approaches. The research results displayed in this article are; at the time of al-Khulafa' al-Rasyidin, there was no standard pattern regarding appointing a caliph or head of state. The pattern of government of al-Khulafa' al-Rasyidun, a government based on deliberation, consistently implemented The mandate of